Gendered patterns in mathematics self-esteem and student perceptions of teacher dispositions - Richmond Kiki Gyan; Farouq Sessah Mensah (Discover Education)
Abstract In mathematics education, self-esteem is increasingly acknowledged as a critical affective variable that shapes students’ academic identity and engagement. However, limited research exists on how classroom experiences influence global self-esteem, particularly in high-stakes and gendered contexts, such as mathematics classrooms in sub-Saharan Africa. This study investigated the relationship between gender, mathematics teachers’ classroom dispositions (supportive vs. controlling), and high school students’ global self-esteem in Ghana’s Shama–Ahanta East Metropolitan area. A predictive correlational research design was employed using the following validated instruments: the Rosenberg Self-Esteem Scale (RSES), Students’ Perception of Teachers’ Controlling Behaviour Scale (SPTCBS), and Students’ Perception of Teachers’ Supporting Behaviour Scale (SPTSBS). A purposive sample of 323 Senior High School (SHS) 3 students was surveyed, and the data were analysed using descriptive statistics, t-tests, and multiple regression analysis. Students reported above-average global self-esteem, with male students scoring significantly higher than female students. Teachers were perceived as more supportive than controlling. A modest but statistically significant predictive relationship was found between self-esteem and the combination of gender and perceived teacher disposition. Teachers’ support had the strongest positive association with self-esteem. While the RSES measures global rather than domain-specific self-esteem, the findings suggest that affective classroom experiences in core mathematics significantly contribute to students’ overall self-concept, especially in performance-driven educational settings such as Ghana. The results highlight the role of gendered classroom dynamics in shaping adolescents’ psychological engagement and suggest the need for culturally responsive relational pedagogies to support equitable mathematics learning environments.